Percepção das mães sobre a qualidade de vida de irmãos de crianças com Transtorno do Espectro Autista - Mattos, Natalia Magalhaes De [UNIFESP] (2019)
The chronic health conditions that affect the child and youth population require a reorganization of the family system. This process can last for days, months or years, and it can change the family dynamics, from financial aspects to those related to the physical, psychological and social quality of life (QoL), as well as values and roles. The increased demand for care and attention is a cause for friction. The process of acceptance, understanding, and adaptation of each family and, more specifically, each member that makes up the familial structure is very particular and depends on multiple social and psychological factors. However, certain types of chronic conditions may affect fraternal relationships. It is possible to think of the difference in the construction of the relationship between the dyad in the face of diseases that present cognitive, language and/or social interaction impairment of those that have exclusively physical limitations. In the case of Autism Spectrum Disorder (ASD), there is impairment in two groups of symptoms: a deficit in communication and social interaction, and a pattern of restricted and repetitive behaviors. Objective: To evaluate the quality of life of siblings of ASD patients from the perspective of mothers. Method: Quantitative-qualitative study using the PedsQLTM 4.0 quality of life questionnaire and a semi-structured interview with the mothers of 26 siblings of children with ASD accompanied at the Social Cognition Outpatient Clinic of the Federal University of São Paulo, conducted between February 2017 to April 2019. Results: The qualitative analysis revealed four main topics: (a) diagnostic process, revelation, and acceptance; (b) support from family members; (c) fraternal relationship, understanding, and involvement of the sibling in the care of the child and impact on the daily life of the family; (d) understanding of the disease. Quantitative and sociodemographic data complemented the information collected in the interviews. Conclusion: The impact of having a sibling with ASD is reflected in routine changes, financial reorganization, and family dynamics. These changes require all family members to psychologically adjust, including siblings. Although they may develop the capacity to understand diversity and its social aspects, family and professional support should lead them to it. There is a gap to be filled in health services for the care and support of siblings of patients with ASD and their families.